The Possibility of Becoming in Pedro Almodóvar's Mujeres al borde de un ataque de nervios (1988) and Los abrazos rotos (2009). Issue 2 (February 2019) - Cacoullos, Anna Torres
Abstract : The persistent, multiform, and seemingly inconsequential visual treatment of fruit by Pedro Almodóvar in the two closely tied films, Mujeres al borde de un ataque de nervios (1988) and Los abrazos rotos (2009), I argue here, draws on the phenomenological ontology of Jean-Paul Sartre. Almodóvar participated in a 1977 Spanish production of Sartre's Dirty Hands (1948), where he would meet Carmen Maura and become familiar with the philosophy of the French existentialist. This early exposure to Sartre, whose phenomenology denies the existence of a fixed ego and an essential self, would exert profound influences on postmodern conceptions of subjectivity and was formative, I sustain, in the director's filmic preoccupation with body politics. Moreover, I argue that the female protagonists of both films overcome Sartrean homogeneity and lack of differentiation ; it is precisely this struggle that constitutes the ground for their freedom from a 'fixed' existence by the men who object-ify them.